Metabolomic study of wild and cultivated caper (Capparis spinosa L.) from different areas of Sardinia and their comparative evaluation. (1st September 2016) - Maldini, Mariateresa; Foddai, Marzia; Natella, Fausta; Addis, Roberta; Chessa, Mario; Petretto, Giacomo Luigi; Tuberoso, Carlo I. G.; Pintore, Giorgio
Abstract : Capparis spinosa L. (Capparidaceae), also known as caper, is widely known for its very aromatic flower buds (capers), that are largely employed as a flavouring in cooking. Capparis species are regarded as a potential source of important bioactive compounds, in fact, due to their botanical relationship with Brassica species; they contain glucosinolates, secondary plant metabolites, that have been studied for their potential anticarcinogenic properties. In addition, the presence of other numerous beneficial compounds such as polyphenols, alkaloids, lipids, vitamins and minerals have been reported. The aim of this study was to individuate and determinate the principal bioactive compounds occurring in different part (leaves, buds and flowers) of wild and cultivated C. spinosa collected from different area of Sardinia (Italy). Ultra‐high performance liquid chromatography‐triple quadrupole/linear ion trap tandem mass spectrometry methods were used for identification and simultaneous determination of 27 bioactive molecules. Analysis of different samples revealed qualitative and quantitative differences in the content of flavonoids, glucosinolates, anthocyanins and phenolic acids. In particular, glucocapparin resulted the most abundant with values ranging from 112 to 364 mg/100 g Fresh Weight (FW); followed by rutin with highest value of 126 mg/100 g FW, 4‐hydroxyglucobrassicin with highest value of 42 mg/100 g FW and isorhamnetin 3‐ O ‐rutinoside with highest value of 24 mg/100 g FW. Based on this metabolomic targeted approach, quantitative results were treated by principal component analysis to explore and visualise correlation and discrimination among collections of C. spinosa samples . Copyright © 2016 John Wiley & Sons, Ltd.